Unemployment: The Measures We Need (Observatorio Económico, 2009)
A few weeks ago the government, employers, and workers signed a cross-cutting agreement “for employment, training, and labor protection.” It comprises a set of measures intended to combat the main fear generated by the global financial crisis: unemployment. But in order to fight it, one must first ask what kind of enemy it is. Continue reading...
Keywords: unemployment; training; labor protection